Good practice for professional coaching. (2nd February 2020) - Webb, Helen
Abstract : Drawing upon the literature and her experience as a professional coach, Helen Webb discusses the importance of effective contracting for in-school coaching programmes, including return on investment, goal-setting, confidentiality and demonstrating impact